Templated Sequence Insertion Polymorphisms in the Human Genome - Onozawa, Masahiro; Aplan, Peter D. (Frontiers in Chemistry, 2016)
Templated Sequence Insertion Polymorphism (TSIP) is a recently described form of polymorphism recognized in the human genome, in which a sequence that is templated from a distant genomic region is inserted into the genome, seemingly at random. TSIPs can be grouped into two classes based on nucleotide sequence features at the insertion junctions; Class 1 TSIPs show features of insertions that are mediated via the LINE-1 ORF2 protein, including 1) target-site duplication (TSD), 2) polyadenylation 10-30 nucleotides downstream of a “cryptic” polyadenylation signal, and 3) preference for insertion at a 5’-TTTT/A-3’ sequence. In contrast, class 2 TSIPs show features consistent with repair of a DNA double-strand break via insertion of a DNA “patch” that is derived from a distant genomic region. Survey of a large number of normal human volunteers demonstrates that most individuals have 25-30 TSIPs, and that these TSIPs track with specific geographic regions. Similar to other forms of human polymorphism, we suspect that these TSIPs may be important for the generation of human diversity and genetic diseases.